The Benefit of Activated Charcoal in Reducing Mortality in Toxic Patient: A Meta-Analysis - Bakhsh, Hussian (International Journal of Innovative Research in Medical Science, 2023)
The objective of the study was to estimate the effect of activated charcoal (AC) administration on the mortality of patients taking toxic materials and the effect of drug properties on drug exposure. Thirty studies were integrated in a meta-analysis. AC administered 0–5 min after administration of a drug reduced median drug exposure by 88.4% (25–75 percentile: 65.0–96.8) (P < 0.00001). The effect of AC continued to be statistically significant when administered up to 4 h after drug intake (median reduction in drug exposure 27.4% (range 21.3–31.5%, P = 0.0006). Furthermore, there were significant decrease in the mortality as long as AC is administered early. The reduction in drug exposure was correlated with the AC/drug ratio (ρ = 0.69, P < 0.0001), the volume of distribution (Vd) (ρ = 0.46, P = 0.0001), and time to peak concentration (ρ = 0.40, P = 0.02). We found that AC is most effective when given immediately after drug ingestion but has statistically significant effects even when given as long as 4 h after drug intake. AC appears to be most effective when given in a large dose. And it affects the mortality in earlier intervention better than late intervention.